2019
DOI: 10.1101/2019.12.16.877613
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary sugar inhibits satiation by decreasing the central processing of sweet taste

Abstract: From humans to flies, exposure to diets rich in sugar and fat lowers taste sensation, changes food choices, and promotes feeding. However, how these peripheral alterations influence eating is unknown. Here we used the genetically tractable organism D. melanogaster to define the neural mechanisms through which this occurs. We characterized a population of protocerebral anterior medial dopaminergic neurons (PAM DANs) that innervates the β'2 compartment of the mushroom body and responds to sweet taste. In animals… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 56 publications
(86 reference statements)
1
17
0
Order By: Relevance
“…Flies on a high sugar diet have lower sweet taste because the neural responses of the taste neurons to sweet stimuli are decreased (14,15). Since Pcl mutants have identical sweet taste sensation on a control and sugar diet ( Fig.…”
Section: Pcl Mutant Animals Have the Same Sensory Responses To Sucrosmentioning
confidence: 99%
See 2 more Smart Citations
“…Flies on a high sugar diet have lower sweet taste because the neural responses of the taste neurons to sweet stimuli are decreased (14,15). Since Pcl mutants have identical sweet taste sensation on a control and sugar diet ( Fig.…”
Section: Pcl Mutant Animals Have the Same Sensory Responses To Sucrosmentioning
confidence: 99%
“…We previously showed that restoration of sweet taste neuron activity in flies fed high dietary sugar protected them from diet-induced obesity (14,15), here defined by an increase in fat mass over protein levels. Since Pcl mutants abolished the deficits in neural and behavioral responses to sweetness in animals fed a high sugar diet, we anticipated that they should also prevent a diet-dependent increase in triglycerides.…”
Section: Pcl Mutant Animals Have the Same Sensory Responses To Sucrosmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans consume more calories when their diets consist of processed foods [198]. It has been shown that reducing taste sensation at the periphery, a high sugar diet impairs the central Dopamine processing of sensory signals and weakens satiation [199]. Given the importance of sensory changes in initiating this cascade of circuit dysfunction, understanding how diet composition mechanistically affects taste is imperative to understand how the food environment directs feeding behavior and metabolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, diet has been shown to change the taste perceptions of animals from insects to humans (Bertino et al, 1982;Glendinning et al, 2001;May et al, 2019a;Stewart and Keast, 2012;Wang et al, 2016;Wise et al, 2016;Zhang et al, 2013) , and across organisms, sensory alterations affect food preference and intake, influencing the development of conditions like obesity and heart disease (Bertino et al, 1982;May et al, 2019a;Stewart and Keast, 2012) . We recently found that high dietary sugar dulls the responses of the fruit fly taste neurons to sweet stimuli, causing higher food intake and weight gain (May et al, 2019a(May et al, , 2019b . Mammals fed high nutrient diets also show changes in taste, neural responses, and food preferences (Ahart et al, 2019;Chen et al, 2010;Crow, 2012;Kaufman et al, 2018;Maliphol et al, 2013;May et al, 2019a;McCluskey et al, 2020;Sartor et al, 2011;Weiss et al, 2019) , arguing that the effects of diet on taste are conserved and promote obesity.…”
Section: Introductionmentioning
confidence: 99%